After the baby boomers: how twenty- and thirty-somethings are shaping the future of American religion - Wuthnow, Robert (Princeton University Press, 2007)
Much has been written about the profound impact the post-World War II baby boomers had on American religion. But the lifestyles and beliefs of the generation that has followed--and the influence these younger Americans in their twenties and thirties are having on the face of religion--are not so well understood. It is this next wave of post-boomers that Robert Wuthnow examines in this illuminating book. What are their churchgoing habits and spiritual interests and needs? How does their faith affect their families, their communities, and their politics? Interpreting new evidence from scores of